2008
DOI: 10.1007/s10528-008-9180-8
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Expression Pattern of Class II and Class V Genes Found in the Adh Complex on Mouse Chromosome 3

Abstract: The alcohol dehydrogenase enzymes in mice and humans are encoded by a linked group of genes in the same transcriptional orientation. The enzymes play important roles in alcohol metabolism and retinoid signaling and homeostasis. The expression patterns at the mRNA level of the mouse Adh4 (class II) gene and the recently identified Adh6a and Adh6b genes (class V) are now reported to complete this analysis for the entire family. Adh4 is expressed at high levels in liver and is detectable in small intestine and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
(33 reference statements)
0
7
0
Order By: Relevance
“…Two activity phenotypes of ADH2 in human duodenal/jejunal mucosae were identified by isoelectric focusing gels. Northern blot analyses have demonstrated that ADH2 mRNA is predominantly expressed in liver, followed by small intestine but considerably lower or undetectable in the other tissues examined, in human and rodents (Estonius et al., , ; Szalai et al., ). Interestingly, only 60% of the intestinal samples in the present study showed ADH2 activity bands.…”
Section: Discussionmentioning
confidence: 99%
“…Two activity phenotypes of ADH2 in human duodenal/jejunal mucosae were identified by isoelectric focusing gels. Northern blot analyses have demonstrated that ADH2 mRNA is predominantly expressed in liver, followed by small intestine but considerably lower or undetectable in the other tissues examined, in human and rodents (Estonius et al., , ; Szalai et al., ). Interestingly, only 60% of the intestinal samples in the present study showed ADH2 activity bands.…”
Section: Discussionmentioning
confidence: 99%
“…This group of genes has been reported to encode for 5 different classes of enzymes in identical transcriptional orientation, and these enzymes can reverse the oxidation of a handful of primary and secondary alcohols to their related ketones and aldehydes, thereby playing essential roles in alcohol metabolism, homeostasis, and retinoid signaling. 1 , 2 The mouse Adh1 gene and human ADH1A, ADH1B, and ADH1C genes encode class I enzymes responsible for ethanol metabolism; class III enzymes are encoded by Adh5 (mouse) and ADH5 (human) genes which are both involved in S-nitrosoglutathione metabolism. 1 , 2 Genes encoding class I and III as well as class IV (mouse Adh7, human ADH7) are all involved in retinoid signaling.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 The mouse Adh1 gene and human ADH1A, ADH1B, and ADH1C genes encode class I enzymes responsible for ethanol metabolism; class III enzymes are encoded by Adh5 (mouse) and ADH5 (human) genes which are both involved in S-nitrosoglutathione metabolism. 1 , 2 Genes encoding class I and III as well as class IV (mouse Adh7, human ADH7) are all involved in retinoid signaling. 2 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations